Comparison of Epidemiology of IMP-type Metallo-β-Lactamase Producing Carbapenem-Resistant Klebsiella pneumoniae vs. Enterobacter cloacae in a Tertiary Care hospital in Japan over 5 years. (4th October 2017) - Ishikane, Masahiro; Hayakawa, Kayoko; Mezaki, Kazuhisa; Katanami, Yuichi; Takaya, Saho; Nagashima, Maki; Sugiki, Yuko; Ohmagari, Norio
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) represents a major public health issue. Although the majority of CRE are IMP-type metallo-β-lactamase (MBL) producing CRE (IMP-CRE) in Japan, studies on its detailed clinico-epidemiological features are limited. Methods: We conducted a retrospective cohort study of all IMP-CRE isolation cases at NCGM between January 2012 and December 2016. Enterobacteriaceae that were resistant to one or multiple agents in the extended-spectrum cephalosporin class and/or that demonstrated elevated MICs (>1 μg/ml) to imipenem and/or meropenem were screened for carbapenemase production based on EUCAST and national guideline. MBL positive isolates were screened for bla IMP by PCR. Clinical characteristics and laboratory findings were obtained from medical records. Using logistic regression, odds ratios (ORs) and 95% confidence intervals (CIs) were estimated to assess clinical characteristics between Klebsiella pneumoniae (KP) and Enterobacter cloacae (EC). Results: We identified 112 cases of IMP-CRE; the majority of them were EC (67 [59.8%]), and KP (31 [27.7%]). The median age (EC: 77 [IQR: 66–86], KP: 75 [64–83]), proportion of male sex (EC: 32 [47.8%], KP: 20 [64.5%]), and age-adjusted Charlson comorbidity index (EC: 5 [IQR: 4–7], KP: 5 [3–8]) were similar between two groups. Also, the median duration days between admission to isolation of CRE (EC: 30 [IQR: 15–68], KP: 33 [21–91]) was similar between two groups. Compared with IMP-EC, in univariate analysis, exposure to glycopeptides within one month prior to isolation of CRE, nasogastric tube use at onset of isolation of CRE, endoscopy procedure before isolation of CRE, and sputum specimens were positively associated with IMP-KP. In multivariate analysis controlled for above univariate findings, age-adjusted Charlson comorbidity index, and duration days between admission to isolation of CRE, independent predictors for IMP-KP were exposure to glycopeptides (OR = 4.3, 95% CI 1.3–14.4, P = 0.02), nasogastric tube use (OR = 3.7, 95% CI 1.3-10.2, P = 0.01), and endoscopy procedure (OR = 3.1, 95% CI 1.1–8.7, P = 0.03). Conclusion: Exposure to glycopeptides, nasogastric tube use, and endoscopy procedure were associated with IMP-KP. IMP-KP were more likely to have health care-associated exposure than IMP-EC. Disclosures: All authors: No reported disclosures.